2021
DOI: 10.1080/09540121.2021.1889954
|View full text |Cite
|
Sign up to set email alerts
|

The PEARL study: a prospective two-group pilot PrEP promotion intervention for cisgender female sex workers living in Baltimore, MD, U.S.

Abstract: HIV remains elevated among female sex workers (FSW) globally, with a number of structural (e.g., poverty, access to care) factors driving these persistently high rates. Pre-exposure prophylaxis (PrEP), a user-controlled prevention method, is a promising means of empowering vulnerable populations to protect themselves and enhance agency. Yet there is a dearth of PrEP research and interventions targeting cisgender women in the United States, and even fewer aimed to reach FSW. We developed and implemented a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Likewise, the flyers provided FRHWs opportunities to discreetly offer clients PrEP information, especially in the context of limited privacy during drop-in and outreach encounters. Given the persistence of HIV-related stigma and the importance of affirming spaces to confidentially sensitize clients towards PrEP [ 5 , 30 ], these strategies must be considered in future implementation of PPT and comparable interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the flyers provided FRHWs opportunities to discreetly offer clients PrEP information, especially in the context of limited privacy during drop-in and outreach encounters. Given the persistence of HIV-related stigma and the importance of affirming spaces to confidentially sensitize clients towards PrEP [ 5 , 30 ], these strategies must be considered in future implementation of PPT and comparable interventions.…”
Section: Discussionmentioning
confidence: 99%
“…higher income from sex without a condom) and includes concerns such as medical mistrust, and avoidance of medication side effects. A PrEP intervention trial among female sex workers (FSW) in Baltimore, MD described similar barriers such as medication side effects and medical mistrust [ 30 ]. While those researchers also described barriers such as difficulty obtaining venipuncture for recommended testing before initiation of PrEP, our study did not capture these barriers, which may be due to the heterogeneity of our participants while the Baltimore study included FSW with a high proportion of prior or current injection drug use [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the same period, female sex workers (FSW) accounted for 12% of new HIV infections globally [1]. It is widely reported that FSW have a high risk of acquiring HIV infection ranging from 12-30 fold compared to other females in the general population [1][2][3][4][5][6]. Given these figures, FSW and other KPs, were singled out in the 2021 political declaration on Acquired Immunodeficiency Syndrome (AIDS) as being at heightened risk of HIV acquisition requiring critical interventions to stem the tide [6].…”
Section: Introductionmentioning
confidence: 99%